Tocharian-Slavic lexical parallels – new comparisons - Václav Blažek (Linguistica Brunensia, 2019)
The article begins with an overview of the previous literature studying the Tocharian-(Balto-)Slavic lexical and morphological parallels was summarized. In this context three new comparisons were presented: 1. Tocharian A kuk*, du. kukäṃ 'heel'; B kuke*, du. kukene id.? ~ Old Church Slavonic kъkъnja 'Schienbein, Unterschenkel', plus Middle Welsh (13th cent.) kukyn, (14th cent.) kygwng/ kygwn/kygwg, Welsh cwgn, pl. cygnau, 'joint, knuckle; knot or joint on stem or root of plant; knot, knur (in wood); link in chain'; Irish cocung 'chain'; 2. Toch. B lasto 'belonging to branches of a shrub' ~ Slavic *lîstъ 'leaf', plus hypothetical Baltic *lišta(s), reconstructed on the basis of Fenno-Volgaic *lešte 'leaf'; 3. Toch. B rīye, A ri 'city' < *dreu̯i̯o- ~ East Slavic *dervьnja 'village', both originally 'wooden'.